SEJARAH DAN PERKEMBANGAN MADRASAH DI INDONESIA - Mohamad Samsudin; Rifda Haniefa (Turats, 2022)
Madrasa is one form of Islamic educational institution that has gone through a long evolutionary process. Starting from the mosque which was used as a means of education, then kuttab, and so on turned into a madrasa. The process of evolution of the madrasa to become an educational institution that is recognized as capable of producing a superior generation of Islam, of course, has not escaped the long journey of history that it has gone through with challenges. Until finally the madrasa arrived at the archipelago, the historical carvings inscribed by Islamic leaders were also full of exhausting struggles. From then until now, and maybe until when, can not be determined. This paper is intended to find out how the history of madrasa, from classical to modern times, from the Middle East to Indonesia, and the challenges faced for its existence. In this study, the authors use research that is library research using written materials that have been published in the form of books and international journals. This research uses a historical and educational approach. The results of the research in this study indicate that in the history of the growth and development of madrasa in Indonesia, there are two momentums that determine the existence of madrasa: first, the 1975 Joint Decree of Three Ministers (SKB 3 Menteri) which became the entry point for the recognition of madrasa as Islamic educational institutions that is equivalent to public schools; second, the National Education System Law Number 2/1989 which makes madrasa not only educational institutions that is equivalent to public schools, more than that, madrasa is recognized as public schools with Islamic characteristics. In other words, madrasa can be said to be "plus public school". On the other hand, this recognition is a matter of pride for the madrasa, but on the other hand it is also a challenge that needs to be proven, whether the madrasa is able to carry out this dual status.